TANGGUNG JAWAB PELAKU USAHA YANG TIDAK MENERAPKAN ASAS ITIKAD BAIK DALAM TRANSAKSI JUAL IPHONE BEKAS DI TENGGARONG - Muhammad Fauzan Efendi; Erna Susanti; Amsari Damanik (Universitas Labuhanbatu, 2025)
The rapid development of technology in Indonesia has significantly increased consumer demand for electronic devices, particularly iPhones, including those traded in the second-hand market. This phenomenon has encouraged the growth of second-hand iPhone trading activities conducted by business actors in Tenggarong City. However, in practice, various legal issues have arisen that are detrimental to consumers, particularly in the form of breach of contract resulting from the failure of business actors to fulfill their legal obligations. This study aims to analyze the forms of breach of contract in second-hand iPhone sale and purchase transactions, as well as the legal consequences for business actors who fail to apply the principle of good faith. The research employs a socio-legal approach using both normative and empirical methods. The findings indicate that business actors do not comply with their obligations as stipulated in Law Number 8 of 1999 on Consumer Protection, particularly Article 7 letter (a), which mandates business actors to act in good faith in conducting their business activities. Such violations are manifested in the failure to provide accurate, clear, and honest information regarding the condition of the second-hand iPhones sold, the failure to honor promises related to warranties or replacement of goods, and the avoidance of responsibility in addressing consumer complaints. Consequently, business actors may be held legally liable for breach of contract and violations of consumer protection laws, resulting in obligations to provide compensation and fulfill consumers’ rights in accordance with applicable laws and regulations.Keywords: Breach of Contract; Good Faith; Consumer Protection; Second-Hand iPhone Transactions